Inventory Management Model under the Lean Warehousing Approach to Reduce the Rate of Returns in SME Distributors - Serna-Ampuero, Maria Antonieta (2022)
Companies in the wholesale sector face the challenge of maintaining a good level of service, so they must have their processes well controlled. The article studies a cleaning products distributor, which has a high rate of returned orders, caused by incomplete orders, late deliveries, and products in poor condition. This has generated a significant economic impact since companies dedicated to wholesale distribution do not have a high-profit margin. Therefore, the goal is to improve warehouse management and the inventory control and recording process through the 5S, ABC classification, and a continuous inventory review model (Q, r). It is expected to reduce picking search time by 53.89%. It is also expected to reduce the inaccuracy of the inventory register to 8.36% and the percentage of stock out to 8%.